Designing Boundary Objects for Virtual Collaboration - Marheineke, Marc (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2016)

Lowering Knowledge BoundariesThrough Collabortion Technology: A Problem Identification (Kundisch, D., Suhl, L., & Beckmann, L., Ed.) - Marheineke, Marc; Habicht, Hagen; Möslein, Kathrin (Multikonferenz Wirtschaftsinformatik (MKWI 2014), 2014)

On the Importance of Boundary Objects for Virtual Collaboration: A Review of the Literature - Marheineke, Marc; Velamuri, Vivek; Möslein, Kathrin (Technology Analysis & Strategic Management, 2016)

Standing in Misunderstanding: Analyzing Boundary Objects’ Effectiveness in Innovation Communities - Marheineke, Marc; Habicht, Hagen; Möslein, Kathrin (R&D Management Conference 2014, 2014)
In this paper we investigate objects that span boundaries to foster mutual understanding in virtual innovation communities. In particular, we study virtual whiteboards (which comprise a mix of boundary objects) in the early phases of the innovation process. Information systems provide new boundary objects for community members which support their non-canonical, collaborative work required for igniting new ideas. Our study follows the two-sided perspective of socio-technical systems theory. From a social perspective, extant literature provides coverage of the roles of boundary objects for collaborative innovation. From a technical perspective, research investigates efficient communication through media, predicting that most efficient communication is achieved when the object’s synchronicity fits the communication requirements. By combining both perspectives, we will analyze the performance of multiple boundary objects (as part of a virtual whiteboard) with respect to the particular communication requirements of each step of the innovation process. Performance is assessed as the degree to which communication boundaries are overcome and mutual understanding is achieved. First, we assume that boundary objects which convey information most effectively perform high in the idea generation phase. Second, we assume boundary objects that converge on meaning most effectively to perform high in the development and evaluation of ideas. Our empirical analysis is based on a multiple case study analysis of (virtual) innovation communities. Data has been collected from users of a virtual whiteboard who participated in collaborative innovation. The data comprises of information on the use of boundary objects in workshops with members of the innovation community. We conclude with managerial and practical recommendations on how to design boundary objects for (virtual) innovation communities to overcome communications boundaries.
WiSo-Import:2015-04-17:5314
Keywords: boundary management; Boundary objects; communication performance; virtual innovation communities

Towards Shared Understanding: Suggesting Priciples for Boundary Objects´Use in Innovation Communities - Marheineke, Marc; Rabes, Karl; Doll, K.; Möslein, Kathrin (Multikonferenz Wirtschaftsinformatik (MKWI), 2016)